The Comanche Empire. - Hamalainen (Hamalainen), Pekka (New Haven : Yale University Press, 2009)
In the eighteenth and early nineteenth centuries, at the high tide of imperial struggles in North America, an indigenous empire rose to dominate the fiercely contested lands of the American Southwest, the southern Great Plains, and northern Mexico. This p.
Trade
NEW
Keywords: Indians of North America -- West (U.S.); Indians of North America -- History; Indians of North America -- Government Relations; United States -- History -- 19th Century; Mexico -- History -- To 1810.